Anti-windup modified proportional integral derivative controller for a rotary switched reluctance actuator - Md Ghazaly, Mariam; Tee, Siau Ping; Zainal, Nasharuddin (Bulletin of Electrical Engineering and Informatics, 2023)
Over the last decade, industrial applications and promising research domains including robotics and automotive engineering have adopted the rotary switched reluctance actuator (SRA). SRA's fault tolerance, simple, strong structure, and high-frequency operation make it popular. However, the SRA's nonlinear magnetic flux flow and saturation operation negate its benefits. Several control systems have been developed; however, they often need extensive mechanism models and advanced control theory, making them impracticable. This paper proposes a modified proportional integral derivative (PID) controller to evaluate the control performance, which comprises of PID controller with an anti-windup, a linearizer unit, and switching mechanism to activate the SRA phases. The linearizer unit aids to compensate for the nonlinear current-displacement relationship. The anti-windup element helps to halt the integral action during the starting motion. At the fully aligned position, 60°, the modified PID reduced positioning steady-state error by 4.3 times at 76.9%, overshoot by 48.8%, and settling time by 25.3%. Both the modified PID and conventional PID showed zero steady-state error at intermediate position, 70°, however the modified PID controller depicted an improved percentage overshoot by 54.5% and settling time by 74.5%. The results show that the modified PID outperforms conventional PID in transient response, steady-state error, overshoot, and settling time.